Kaleidoscope visualization of fine-grain parallel programs - Evan Tick; Daesun Park (HICSS'92: Proceedings of the Hawaii International Conference on System Sciences, 1992)
A software visualization tool is described that transforms program execution trace data from a multiprocessor into a single, color image. The image is essentially the program's logical procedure-invocation tree, displayed radially from the root. An algorithm is described that condenses the image both radially and laterally, producing a color-dense abstraction of the program's execution behavior: a program signature, within a workstation window. An implementation of the tool was made in X-Windows, including a user interface that can zoom the image and annotate any node in the image with the corresponding procedure-invocation data. Experimentation with the system was performed with trace data from Panda, a concurrent logic programming system on shared-memory multiprocessors. The authors demonstrate how the tool helps the programmer develop intuitions about parallel performance and how condensation successfully abstracts very large traces.